Exploring Airbnb Host Wellbeing and Host-Guest Conflicts in Network Hospitality - Ozanne, Lucie K.; Prayag, Girish (Frontiers in Psychology, 2022)
Despite a plethora of studies examining hosting experiences of Airbnb guests, the well-being of hosts has received limited attention. Drawing on both top-down and bottom-up theories of well-being, we explore the different ways in which Airbnb enhances or diminishes host well-being using a multidimensional lens (material, relational and subjective well-being). Data is collected from in-depth interviews with twenty-two Airbnb hosts. We also identify tensions and conflicts in the host-guest relationship using the three interactional hospitality domains of commercial, social and private. Through a deductive process, we find that participating in Airbnb both enhances and diminishes the material, relational and subjective aspects of well-being for hosts. Inductively, we find that a lack of territorial boundaries in shared accommodation contribute to conflicts that reduce well-being. This exemplifies a tension that exists in the private-commercial domain of network hospitality provision. We provide implications for peer-to-peer accommodation providers on developing the managerial skills of hosts, and helping hosts set realistic expectations around hosting to reduce the conflicts and tensions that arise from the intersectionality of the various Airbnb hospitality domains in such a way that the well-being of hosts is enhanced.